Travelling after amniocentesis: Answer to a frequent question. (May 2013) - Karaşahin, K. E.; Ozturk, M.; Çoksuer, H.; Torun, D.; Tunca, Y.
<x xml:space="preserve">Abstract</x> The study investigated whether travelling after amniocentesis has an effect on outcomes of the procedure. A total of 57 patients who were referred to our tertiary centre from distant cities and who had to travel back by bus, by car or by plane, were evaluated for amniocentesis outcomes. The travelled distances were divided into 3 zones, which consisted of 50–100, 101–300 and over 300 km. Patients (n = 85) residing in our city (within 50 km) were identified as the control group. All of the procedures were done by the same perinatology team, following exactly the same procedure. It was found that there was one transient amniotic fluid leakage patient who had travelled 70 km by car after the amniocentesis. No other patients who had to travel after amniocentesis had a complication related to the procedure. It was concluded that although done on a limited number of patients, this study provides the first scientifically supported evidence that travelling by bus, by car or by plane after amniocentesis does not have adverse effects on the outcomes.